Integrasi Kebijakan Strategis dalam Pengembangan Rumah Sakit : Studi Kasus pada Rumah Sakit Islam Faisal Makassar - Andi Mu’tiah Sari; Erlina HB; Asmiana Saputri Ilyas (Universitas Muhammadiyah Manado, 2024)
Hospitals play a strategic role in improving public health through high-quality healthcare services. To achieve this goal, hospitals must develop strategic policies covering various aspects, such as services, infrastructure, and human resource management. The effective implementation of strategic policies requires thorough planning, resource optimization, and adaptation to scientific and technological advancements. This study aims to examine the integration of strategic policies in the development of Faisal Islamic Hospital Makassar, using a qualitative approach with a case study method. The findings indicate that the hospital implements long-term strategic planning oriented toward community needs, enhances the competence of medical personnel, and develops infrastructure and technology to improve service efficiency. Additionally, funding strategies involving collaboration with various stakeholders and compliance with national health regulations are crucial factors in hospital management. However, in practice, the hospital faces several challenges, including budget constraints, a shortage of specialist medical personnel, and regulatory changes requiring quick adaptation. To address these challenges, Faisal Islamic Hospital Makassar adopts policy-strengthening strategies, such as enhancing cooperation with the government and private sector, optimizing digital technology, and formulating flexible internal policies that remain aligned with national regulations.